2010
DOI: 10.1111/j.1651-2227.2010.02044.x
|View full text |Cite
|
Sign up to set email alerts
|

Children and youth with myelomeningocele’s independence in managing clean intermittent catheterization in familiar settings

Abstract: Interviews were not sufficiently accurate to assess independence in the toilet activity. Instead, observations including time to completion are recommended. The execution of the toilet activity is influenced by the environmental context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Both lower levels are needed to learn the highest level: time management (25). There is also evidence to support the relation of time-processing ability to everyday functioning including managing one's time (23,26).…”
Section: Interventions To Support Difficulties In Managing Timementioning
confidence: 95%
“…Both lower levels are needed to learn the highest level: time management (25). There is also evidence to support the relation of time-processing ability to everyday functioning including managing one's time (23,26).…”
Section: Interventions To Support Difficulties In Managing Timementioning
confidence: 95%
“…It is shown that time perception influences the possibility for independence and participation (13). The observation of 50 children with MMC also showed that time orientation was most often normal but time perception and time management lowered compared with peers of the same ages (12). It is obvious that toilet procedures with CIC and TRI (trans-rectal irrigation) are more time-consuming compared with how long healthy children spend at the toilet.…”
Section: Introductionmentioning
confidence: 93%
“…Half of the children were independent but far from what might be expected in relation to age and cognitive and physical status of the child (12). It is shown that time perception influences the possibility for independence and participation (13).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations